Gryphons aren't so great - Sturm, James, 1965- (Sturm, James, 1965- Adventures in cartooning Jr., 2015)
"The Knight's best friend is her horse, Edward. They go everywhere together and do everything together! But when the Knight gets a gryphon, suddenly all she talks about is how awesome her new pet is. Edward can't help it--he's jealous! But the gryphon turns out to be more of a peril than a pet, and it's Edward who comes to the rescue in the end. It turns out that gryphons aren't so great...but Edward sure is!" -- provided by publisher.